BASIC DIDACTIC PRINCIPLES IN THE PROCESS OF TEACHING THE SCIENCE OF DRAWING - Nurbek Norboyugli Achilov (Galaxy International Interdisciplinary Research Journal, 2022)
Based on the teaching of the drawing lesson, ideas about didactic principles and teaching methods were given and shown. Today, to increase the effectiveness of the lesson and its quality, it is necessary to use the methods of transfer of principles widely. That is why this article focuses on these issues.